Architecture Considerations of LTE/WCDMA Wideband Power Amplifier for Efficiency Improvement (Global Journal of Computer Science and Technology, 2019)
An enhanced architecture for a broadband power amplifier (PA) for LTE and WCDMA handsets using In GaP/Ga As hetero-junction bipolar transistor (HBT) process is presented. A two-stage PA solution adopting switchable driver-stage amplifier without employing input switch is proposed to reduce loss and help with power efficiency improvement. Furthermore, in order to enhance the power-added efficiency (PAE) at the low output power level, a two-chain amplifying structure in parallel has been implemented. For wideband 1.71-1.98GHz, the fabricated PA shows 27dB of Gain and 38% of PAE with 80mA of quiescent current (Icq) at the output power (Pout) of 28dBm for high-power mode operation, as well as 16dB of Gain and 13% of PAE with 20mA of Icqat the Pout of 17dBm for low-power mode operation. The system power usage efficiency are obviously enhanced with the presented two-stage dual-chain PA architecture.